Pengaruh Customer Relationship Management, Pengalaman Pelanggan dan Kepercayaan Merek terhadap Loyalitas Pelanggan di Starbucks Kelapa Gading - Ujang Yudi; Hadi Wasino (LPPM Universitas Asa Indonesia, 2023)
In the midst of increasingly intense business competition, it is not an easy task for companies to sustain their business, knowing that the company's focus is not only on how to increase sales but also on acquiring loyal customers. The aim of this research is to determine the influence of customer relationship management (CRM), customer experience, and brand trust on customer loyalty at Starbucks Kelapa Gading. Data collection was conducted by distributing questionnaires to consumers. The sampling technique used was purposive sampling with a total of 200 respondents. This research employed a hierarchical structural model to test the proposed hypotheses, using the SEM (Structural Equation Modeling) analysis technique. The data processing for this research was performed using SmartPLS version 3.2 software. The results of this study demonstrate a significant direct influence of customer relationship management (CRM), customer experience, and brand trust on customer loyalty.